1997
DOI: 10.1029/97jb01589
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of crustal anatexis: Implications for the growth and differentiation of continental crust

Abstract: Abstract. Them is overwhelming and incontrovertible petrological and geophysical evidence for the significant role played by mantle-derived mafic magma in the generation and growth of continental crust. Likewise, intrusion of mafic magmas beneath or into continental crust is very likely the major source of enthalpy that drives intracrustal differentiation. A simple dynamical model has been constructed to examine the critical factors that govern the evolution and timescale of crustal anatexic events when driven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 89 publications
1
14
0
Order By: Relevance
“…Furthermore, the NDC, which are mainly composed of the Neoproterozoic (700-800 Ma) orthogneisses (>90% felsic gneisses; Liou et al, 2009), has been identified as the main composition of the lower continental crust of the Dabie orogen before it was thinned or destroyed . Because the gneisses are widely migmatited in the NDC, which is considered as an anatexis of the lower continental crust (e.g., Raia and Spera, 1997). Thus the gneisses in the NDC seem the most likely source rocks for the Tiantangzhai adakitic granites.…”
Section: Whole-rock Geochemistrymentioning
confidence: 99%
“…Furthermore, the NDC, which are mainly composed of the Neoproterozoic (700-800 Ma) orthogneisses (>90% felsic gneisses; Liou et al, 2009), has been identified as the main composition of the lower continental crust of the Dabie orogen before it was thinned or destroyed . Because the gneisses are widely migmatited in the NDC, which is considered as an anatexis of the lower continental crust (e.g., Raia and Spera, 1997). Thus the gneisses in the NDC seem the most likely source rocks for the Tiantangzhai adakitic granites.…”
Section: Whole-rock Geochemistrymentioning
confidence: 99%
“…Models of heat transfer between mafic magma and crust have typically involved a single mafic sill instantaneously emplaced in contact with crustal rocks (Barboza & Bergantz 1996;Bergantz 1989;Huppert & Sparks 1988;Jackson et al 2003;Raia & Spera 1997). The amount of crustal melt generated in these models depends on the thickness of the mafic sill, and on the initial temperatures and physical properties of the mafic magma and crust.…”
Section: Progressive Emplacement Of Mafic Magmamentioning
confidence: 99%
“…The melting of continental crust can be achieved via two fundamental mechanisms: either by advective heating resulting from basalt underplating or intrusion (Huppert & Sparks, 1988;Bergantz, 1989;Raia & Spera, 1997) or via thickening of crust rich in heat-producing elements (England & Thompson, 1984), assisted or not by shear heating (Le Fort, 1975;England et al, 1992;Harrison et al, 1998) or isothermal decompression (Harris & Massey, 1994). The Himalaya range is a collisional belt characterized by the production of crustal melts without the involvement of basalt .…”
Section: Introductionmentioning
confidence: 99%